2020
DOI: 10.2147/dmso.s275987
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Ten-Year Review of the Pattern and Outcome of Childhood Diabetes in Two State Teaching Hospitals in South-West Nigeria</p>

Abstract: Background Childhood diabetes mellitus is a poorly researched topic in Nigeria. Its contribution to morbidity and mortality is vague. This study intends to provide additional information to the background data in Nigeria and hopefully proffers strategies to improving the outcome of this disease. Methods This is a retrospective descriptive study of all children managed for childhood diabetes mellitus at the Ekiti State University Teaching Hospital (EKSUTH) and LAUTECH Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
1
0
0
Order By: Relevance
“…Their conclusion was supported by their findings of a female: male ratio amongst the newly diagnosed T1D (with DKA) of closer to an equal sex distribution, and the number of admissions involving females with recurrent episodes of DKA being almost double that of males. Majority of our study population were adolescents aged 10-15years, in agreement with reports from Nigeria [10,29], other African countries [1,19] and Asia [5,26,27], probably because majority of our study population were 10 years and above at the time of diagnosis of T1D and they either presented with DKA at time of diagnosis or at a later time, thus diabetes was more frequently diagnosed in adolescents than younger children in our series and this also applies to DKA, a complication of T1D.…”
Section: Discussionsupporting
confidence: 91%
“…Their conclusion was supported by their findings of a female: male ratio amongst the newly diagnosed T1D (with DKA) of closer to an equal sex distribution, and the number of admissions involving females with recurrent episodes of DKA being almost double that of males. Majority of our study population were adolescents aged 10-15years, in agreement with reports from Nigeria [10,29], other African countries [1,19] and Asia [5,26,27], probably because majority of our study population were 10 years and above at the time of diagnosis of T1D and they either presented with DKA at time of diagnosis or at a later time, thus diabetes was more frequently diagnosed in adolescents than younger children in our series and this also applies to DKA, a complication of T1D.…”
Section: Discussionsupporting
confidence: 91%
“…This was similar to studies conducted in some parts of Nigeria and agreed with the study conducted in Saudi Arabia that showed that the condition occurred more among adolescents. 17,27,28,34 The mean and standard deviation were 14±2.83years and this was similar with studies conducted in Saudi Arabia and some parts of Nigeria. 17,28,22,29,35 There was no family history of DM in 45.0% of the study population while 30.0% had family members with DM.…”
Section: Discussionsupporting
confidence: 88%